2013
DOI: 10.1038/srep02054
|View full text |Cite
|
Sign up to set email alerts
|

Cold-induced RNA-binding proteins regulate circadian gene expression by controlling alternative polyadenylation

Abstract: The body temperature is considered a universal cue by which the master clock synchronizes the peripheral clocks in mammals, but the mechanism is not fully understood. Here we identified two cold-induced RNA-binding proteins (RBPs), Cirbp and Rbm3, as important regulators for the temperature entrained circadian gene expression. The depletion of Cirbp or Rbm3 significantly reduced the amplitudes of core circadian genes. PAR-CLIP analyses showed that the 3′UTR binding sites of Cirbp and Rbm3 were significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
185
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(202 citation statements)
references
References 51 publications
(67 reference statements)
10
185
7
Order By: Relevance
“…The stability of CIRBP target mRNAs has been shown to be increased in testis (29). CIRBP represses the usage of proximal polyadenylation sites by binding to the common 3Ј-UTRs (12). It has been proposed that down-regulation of CIRBP leads to the preferred use of the proximal polyadenylation sites and shortening of 3Ј-UTR (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of CIRBP target mRNAs has been shown to be increased in testis (29). CIRBP represses the usage of proximal polyadenylation sites by binding to the common 3Ј-UTRs (12). It has been proposed that down-regulation of CIRBP leads to the preferred use of the proximal polyadenylation sites and shortening of 3Ј-UTR (12).…”
Section: Discussionmentioning
confidence: 99%
“…High amplitude expression of transcripts associated with circadian clock function has been found to depend on CIRBP. Among the transcripts interacting with CIRBP are the mRNAs encoding Sirtuin-1 (SIRT1), PER2, PER3, and DBP, which were decreased in Cirbp-depleted cells (10,12). The phenotype caused by Cirbp deficiency resembles most closely that observed in cells depleted of Clock.…”
mentioning
confidence: 96%
“…3) is consistent with the reduced amplitude of the core body temperature rhythm when sleeping out of phase. CIRBP and RBM3 potentially regulate the circadian expression of several thousands of genes, which include core circadian clock genes and genes involved in the regulation of gene expression, such as genes for RNA polymerase II and ribosomal protein subunits (10,49). In fact, comparison between the list of transcripts whose expression showed an interaction between sleep condition and time with published lists of gene targets for CIRBP and RBM3 (49) showed an ∼30% overlap ( Fig.…”
Section: Mechanisms Underlying the Temporal Disruption Of Gene Expresmentioning
confidence: 99%
“…Thus, the amplitude of the temperature rhythm is high when the temperature lowering effect of sleep coincides with the circadian phase during which melatonin is synthesized (i.e., the biological night), and the overt core body temperature amplitude is lower when sleep occurs during the biological day (48). Therefore, a potential mechanism for the observed effects of desynchrony would be that the lowered amplitude of core body temperature caused by sleeping out of phase affects the amplitude of rhythmicity in temperature-sensitive RNA-binding proteins, such as cold-inducible RNA-binding protein (CIRBP) and RNA-binding motif protein 3 (RBM3), which control the expression of key circadian regulators of transcription and translation (10,49). CIRBP and RBM3 are both induced by lower temperature, and the observed change in the time course of expression in these transcripts when sleeping in and out of phase with melatonin (Fig.…”
Section: Mechanisms Underlying the Temporal Disruption Of Gene Expresmentioning
confidence: 99%
“…iCLIP studies previously showed that mRNA targets of these 2 cold-induced proteins have enriched binding sites near polyadenylation sites and reduced expression of CIRBP and RBM3 resulted in shortened 3 0 UTRs. 37 …”
Section: Alternative Polyadenylationmentioning
confidence: 99%